Acupuncture Activates ERK-CREB Pathway in Rats Exposed to Chronic Unpredictable Mild Stress. (17th June 2013) - Lu, Jun; Liang, Jia; Wang, Jun-Ren; Hu, Li; Tu, Ya; Guo, Jian-You
Abstract : Extracellular signal-regulated kinase (ERK)-cAMP response element binding protein (CREB) signal pathway has been implicated in the pathogenesis of depression. There is growing evidence that acupuncture in traditional Chinese medicine has antidepressant-like effect. However, the effect of acupuncture on ERK-CREB pathway remains unknown. In our study, the antidepressant-like effect of acupuncture treatment was measured by sucrose intake test and open field test in rats exposed to chronic unpredictable mild stress (CUMS) for 4 weeks. The protein levels of ERK1/2, CREB, phosphorylated ERK1/2 (p-ERK1/2), and phosphorylated CREB (p-CREB) in the hippocampus (HP) and prefrontal cortex (PFC) were examined by Western blot analysis. Our results showed that CUMS rats exhibited the reduction in behavioral activities, whereas acupuncture stimulation at acupoints Baihui (Du20) and Neiguan (PC6) reversed the behavioral deficit. In addition, exposure to CUMS resulted in the decrease of p-ERK1/2 and p-CREB in the HP and PFC. Acupuncture increased the ratio of p-ERK1/2 to ERK1/2 and the ratio of p-CREB to CREB in the HP and PFC. Our study suggested that one potential way, by which acupuncture had antidepressant-like effect, might be mediated by activating the ERK-CREB pathway in the brain.